(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of this research work is to prepare novel eatable gel formulations with suitable rheological characteristics,which provide a means of administering salbutamol sulphate to dysphagic and geriatric patients. Gels prepared using a natural polymer silk fibroin of different concentrations was subjected for in vitro characterization.The effect of concentration of the solution on gelation time, viscosity, and drug release was studied. FTIR and DSC spectra reveal that the drug was found compatible with silk fibroin. TGA curves showed weight loss as the temperature increased. Formulations F3, F4, F6, and F9 had thin, nectar like, honey like, and spoon thick viscosity range respectively, which is considered suitable for dysphagia patients as given by National Dysphagia Diet Task Force. Formulations showed shear thinning pseudoplastic behavior. Based on the concentration and viscosity of the polymer, formulation F9 was found to sustain the release of drug up to 90 min (99.4 ± 0.5%), whereas F3 showed release within 5 min (99.2 ± 2.0%). Mechanism of drug release was found to be anomalous transport. All formulations were found stable after 6 months when kept at refrigerated temperature (4°C – 8°C) and room temperature. It can be concluded that the salbutamol sulphate gels prepared are suitable as vehicles for dysphagic patients.